Environmental controls, oceanography and population dynamics of pathogens and harmful algal blooms: connecting sources to human exposure - Minnett Peter; McGillicuddy Dennis J; Lerczak James; Laws Ed; Holland Fred; Hitchcock Gary; Dusek Eva; Bienfang Paul; Dyble Julianne; Moore Stephanie K; O'Kelly Charles; Solo-Gabriele Helena; et al. (BMC, 2008)
Abstract Coupled physical-biological models are capable of linking the complex interactions between environmental factors and physical hydrodynamics to simulate the growth, toxicity and transport of infectious pathogens and harmful algal blooms (HABs). Such simulations can be used to assess and predict the impact of pathogens and HABs on human health. Given the widespread and increasing reliance of coastal communities on aquatic systems for drinking water, seafood and recreation, such predictions are critical for making informed resource management decisions. Here we identify three challenges to making this connection between pathogens/HABs and human health: predicting concentrations and toxicity; identifying the spatial and temporal scales of population and ecosystem interactions; and applying the understanding of population dynamics of pathogens/HABs to management strategies. We elaborate on the need to meet each of these challenges, describe how modeling approaches can be used and discuss strategies for moving forward in addressing these challenges.